Memahami Interaksi Sosial Mahasiswa di Perguruan Tinggi: Studi Kasus di Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sumatera Utara - Salimatul Islamiyah; Annisa Nurul Fadilah; Yusra Faizah; Arlina Arlina (Badan Penerbit STIEPARI Press, 2024)
This research aims to investigate students' social interactions in higher education and the factors that influence these interactions. The research results show that some students experience difficulties in interacting due to the large number of assignments and academic competition. Apart from that, cultural differences and fear of other people's judgment also become obstacles for some students in interacting. This research also found that participation in student organizations can increase students' social interactions, as well as influence a person's social interaction behavior. The conclusion of this research is that students' social interactions in higher education are influenced by several factors, including assignments, academic competition, cultural differences, and fear of other people's judgment.